A New Sum Analogous to Gauss Sums and Its Fourth Power Mean - Shaofeng Ru; Wenpeng Zhang (The Scientific World Journal)
The main purpose of this paper is to use the analytic methods and the properties of Gauss sums to study the computational problem of one kind of new sum analogous to Gauss sums and give an interesting fourth power mean and a sharp upper bound estimate for it.